Classroom Management Approaches For Management Students In Learning Process - Romadhon, Muhammad Syahru; Padil, Moh.; Tharaba, M. Fahim (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to describe various classroom management approaches and the steps to implement them in the classroom. This research uses a literature study research method by processing primary data sourced from various reference articles and books. The results of this study are related to the understanding of the classroom management approach which is a teacher's perspective on classroom management activities to make the class more effective. The types of approaches include the authoritarian approach, intimidating approach, permissive approach, behavior change approach, and cookbook approach. From these various approaches, researchers suggest that educators use various classroom management approaches according to their needs and not only use one classroom management approach.